The Impact of COVID-19 Pandemic on Intestinal Parasite Frequency: A Retrospective Study - Aydemir, S.; Afshar, M.T.; Şahin, M.; Cengiz, Z.T.; Elasan, S.; Barlık, F.; Ateş, N. (Yuzuncu Yil Universitesi Tip Fakultesi, 2023)
During the COVID-19 pandemic, countries have closed their borders, banned travel, and restricted human mobility even outdoors in order to control the infection. It is not known whether the measures taken to control the pandemic in Türkiye affect the prevalence of intestinal parasitic infections. This study was conducted to evaluate the effect of the COVID-19 pandemic on the prevalance of intestinal parasites. In the study, the parasitological data of 18,204 patients who applied to Dursun Odabaş Medical Center between June 2018 and December 2021 and whose stool samples were sent to the parasitology laboratory were evaluated retrospectively. Intestinal parasites were detected in 1214(9.89%) of 12270 patients in the pre-COVID-19 period and in 866 (14.59%) of 5934 patients during the COVID-19 period. In the statistical evaluation, it was observed that there was a significant difference between the positivity rate in the pre-COVID-19 period and the positivity rate in the COVID-19 period. On species basis, there was a decrease in the rates of pathogenic parasites G. intestinalis and E. histolytica, but an increase in the rate of B. hominis, which is discussed to be pathogenic. It has been concluded that the decrease in the rate of pathogenic parasites transmitted by fecal-oral route is since the general hygiene rules and the decrease in human-to-human contact are effective in the COVID-19 period. © 2023, Yuzuncu Yil Universitesi Tip Fakultesi. All rights reserved.
Keywords: Covid-19; Parasite; Van/Türkiye; Adolescent; Adult; Article; Blastocystis Hominis; Child; Coronavirus Disease 2019; Entamoeba Histolytica; Enterobius Vermicularis; Enzyme Linked Immunosorbent Assay; Feces Analysis; Female; Giardia Intestinalis; Human; Infant; Intestine Parasite; Male; Newborn; Pandemic; Positivity Rate; Prevalence; Retrospective Study; Young Adult